Analysis of Physics Students' Conceptual Understanding of Image Formation in Lenses - Hidayat, Wahyu Noor; K, Ronno C; Alé, Jhon Alfredo Silva (Schrödinger: Journal of Physics Education, 2024)
Purpose of the study: This research aims to analyze physics students' understanding of the concept of image formation in lenses.Methodology: This method uses qualitative methods with a research design, namely documentation studies, data collection instruments using interview sheets with data analysis techniques, namely the Miles and Huberman technique.Main Findings: Based on the research results, it can be seen that the level of students' conceptual understanding of image formation is increasing. This is shown by the number of student respondents who answered correctly during the written test, the number increased during the interview test and the average number of respondents who answered correctly was more than half of the total number of respondents. The increase in understanding of this concept occurred because the student respondents were better prepared when taking the interview test than when taking the written test. The respondent students were better prepared because the respondents' memories were revived after the written test.Novelty/Originality of this study: This innovative approach not only highlights the importance of active learning strategies in education but also underscores the potential of sequential testing to foster deeper conceptual understanding among students.